Preparation method of degradable and recyclable plastic

Through esterification reaction and ring-opening metathesis polymerization technology, degradable recycling plastics were prepared, which solved the problem of difficult degradation and recycling of polyolefin plastics, achieved efficient resource recovery and improved mechanical properties, and replaced traditional polyolefin materials.

CN119219898APending Publication Date: 2024-12-31ZHEJIANG UNIV

Patent Information

Application Number
CN202411344074.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The prior art is difficult to effectively degrade and recover polyolefin plastics, resulting in waste of resources and environmental pollution, and has high production costs and low mechanical properties, which cannot replace traditional polyolefin materials.

Method used

Through the esterification reaction, the cyclopentene matrix is ​​synthesized into monomers with alkyl alcohols or alkyl acids, and the ring-opening metathesis polymerization is carried out under the action of a catalyst to obtain a degradable recycling plastic, which can be degraded and resolved back to the original monomer under mild conditions. Achieve 100% recycling of carbon resources.

Benefits of technology

The prepared biodegradable plastic is close to low-density polyethylene in terms of mechanical properties, and can degrade under mild conditions, realize resource recovery, reduce production costs, and replace traditional polyolefin materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219898A_ABST
    Figure CN119219898A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of degradable and recyclable plastic, and belongs to the technical field of polymer preparation. The preparation method comprises the following steps: carrying out esterification reaction on a cyclopentene matrix and alkyl alcohol or alkyl acid to obtain a monomer, and then carrying out ring-opening metathesis polymerization under the action of a catalyst to obtain the degradable and recyclable plastic. The mechanical property of the degradable plastic is close to that of low-density polyethylene, and the degradable plastic can be used for manufacturing packaging bags, so that the degradable plastic can replace LDPE which is difficult to degrade in the packaging field. The degradable plastic prepared by the preparation method disclosed by the invention can be degraded to original monomers under mild conditions, so that 100% recovery of carbon resources is realized. The obtained monomer can be polymerized again to obtain a corresponding polymer, so that closed-loop recycling is realized. The degradable plastic prepared by the invention can be efficiently converted into a plurality of functional polymer materials, and high-value conversion of waste plastic can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer preparation, and in particular relates to a method for preparing degradable and recyclable plastic. Background Art

[0002] Plastic products are the most widely used polymer materials in daily production and life, and are widely used in materials such as packaging, containers, bottles, pipes and high-performance fibers. Due to its mature production technology, relatively simple industrial manufacturing, high cost performance, and good mechanical properties, plastics have not been replaced so far. Among the polymers used in plastic products, polyolefins (polyethylene and polypropylene) account for about 36%, and others include polyethylene terephthalate (PET), which is completely composed of chemical bonds such as CH, CC, CO, and is extremely difficult to break and degrade under natural conditions. Since it is difficult to degrade naturally and the demand will exist for a long time or even increase, it is very necessary to study its effective artificial degradation treatment.

[0003] At present, although there have been many studies on the synthesis and recycling of degradable plastics, such as ethylene-vinyl acetate copolymer (EVA), polycarbonate (PC), polylactic acid (PLA), polyesters, polyethylene / starch blends, and easily degradable linear low-density polyethylene with photosensitizers, these materials themselves have insurmountable defects, such as high production costs, low mechanical properties, low light transmittance, and slow degradation, which have led to their production not being able to fully replace the highly cost-effective polyolefin materials. Therefore, there are still many polyolefin materials with large stocks, large industrial-scale production, and low cost, and research on low-pollution treatment of the environment after their use is still very urgent.

[0004] For a long time, the environmental protection concept of "turning waste into treasure" has been deeply rooted in people's hearts. Polyolefin waste contains a lot of carbon. Both landfill and incineration methods are difficult to truly and efficiently utilize polyolefin plastic waste as carbon resources. Monomers used to produce polyolefins, such as ethylene and propylene, all come from fossil carbon resources such as petroleum or coal. Their reserves are limited and will be exhausted in the foreseeable future. The production of living materials, such as fuels such as gasoline and kerosene, and industrial products such as lubricants and asphalt, will also face difficulties due to the inability to find refining resources. Faced with waste including plastics, rubber, fibers, etc., if the scientific community develops and utilizes them as carbon resources, it will not only have considerable environmental benefits, but also considerable economic benefits. Therefore, the research on the degradable treatment of polyolefins is of significant urgency and has very bright development and application prospects.

[0005] At present, the reported technical solutions for chemical degradation of polyolefin plastics mainly include oxidative cracking, catalytic cracking using molecular sieves (zeolites) and metal organic catalysts to catalyze polymer dehydrogenation, produce carbon-carbon double bonds, and degrade them into low molecules or small molecules based on double bonds and olefin metathesis reactions. However, the carbon utilization rate of oxidative cracking is low (about 37%), and the operating process and equipment requirements are high. Due to excessive oxidation during the process, a large amount of carbon dioxide may even be emitted, and the substrate may be cross-linked or even carbonized, resulting in a waste of resources. Catalytic cracking methods using molecular sieves (zeolites) still need to be carried out at 300°C and a hydrogen pressure of about 170psi, which is a relatively harsh condition. The above catalysts for cracking polymers cannot be recovered or reused, and the technical cost is relatively high. Metal organic catalysts have poor tolerance to impurities and do not have a good use value for waste plastics recovered under real conditions. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention provides a method for preparing a degradable and recyclable plastic.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] The invention provides a method for preparing a degradable and recyclable plastic, comprising the following steps: esterifying a cyclopentene base with an alkyl alcohol or an alkyl acid to obtain a monomer, and then performing ring-opening metathesis polymerization under the action of a catalyst to obtain the degradable and recyclable plastic.

[0009] As a preferred technical solution of the present invention, the cyclopentene base includes one of 3-cyclopentene-1-carboxylic acid, 3-cyclopentene-1-methanol and 3-cyclopentene-1-ol.

[0010] As a preferred technical solution of the present invention, when the cyclopentenyl base is 3-cyclopentene-1-methanol or 3-cyclopentene-1-ol, the corresponding alkyl acid includes one or more of octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosyl acid, docosyl acid, tetracosyl acid, hexacosyl acid, octacosyl acid, triacontyl acid and tridodecyl acid; when the cyclopentenyl base is 3-cyclopentene-1-carboxylic acid, the corresponding alkyl alcohol includes one or more of octyl alcohol, nonanol, decanol, undecyl alcohol, dodecyl alcohol, tetradecyl alcohol, hexadecyl alcohol, octacosyl alcohol, eicosyl alcohol, docosyl alcohol, tetracosyl alcohol, hexacosyl alcohol, octacosyl alcohol, triacontyl alcohol and tridodecyl alcohol.

[0011] As a preferred technical solution of the present invention, the solvent for the esterification reaction includes one or more of dichloromethane, tetrahydrofuran, N,N-dimethylformamide and toluene; the solvent for the ring-opening metathesis polymerization includes one or more of dichloromethane, tetrahydrofuran, toluene, chlorobenzene and dichlorobenzene.

[0012] As a preferred technical solution of the present invention, the catalyst includes Grubbs first generation catalyst, Grubbs second generation catalyst, Grubbs third generation catalyst, Hoveyda-Grubbs first generation catalyst or Hoveyda-Grubbs second generation catalyst.

[0013] As a preferred technical solution of the present invention, the temperature of the ring-opening metathesis polymerization is -10 to 0°C.

[0014] The present invention also provides a degradable and recyclable plastic prepared according to the above-mentioned preparation method.

[0015] The present invention also provides a degradation method for the above-mentioned degradable and recyclable plastic, wherein the degradable and recyclable plastic is added into a solvent and degraded under the action of a catalyst to obtain a monomer.

[0016] As a preferred technical solution of the present invention, the solvent includes tetrahydrofuran, dichloromethane, toluene, chlorobenzene, dichlorobenzene or n-hexane; the catalyst includes Grubbs first-generation catalyst, Grubbs second-generation catalyst, Grubbs third-generation catalyst, Hoveyda-Grubbs first-generation catalyst or Hoveyda-Grubbs second-generation catalyst.

[0017] As a preferred technical solution of the present invention, the degradation temperature is 23-80° C., and the specific degradation temperature can be selected according to the boiling point of the selected solvent and the applicable activity of the catalyst.

[0018] Temperature is a key factor affecting monomer polymerization and polymer degradation, that is, low temperature is conducive to monomer ring-opening polymerization, and high temperature is conducive to polymer degradation into monomers.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention selects cyclopentene, which is relatively abundant in the petrochemical industry, as a matrix raw material to synthesize corresponding crystalline monomers. The present invention polymerizes such monomers to obtain a crystalline polymer material. The crystallization behavior of the polymer material has a very clear linear relationship with the length of the attached side chain. Therefore, the crystallization behavior of the material can be regulated by adjusting the length of the side chain, thereby regulating the mechanical properties of the material.

[0021] (2) The biodegradable plastic prepared by the present invention has mechanical properties close to those of low-density polyethylene (LDPE) and can be used to make packaging bags, thereby replacing the difficult-to-degrade LDPE in the packaging field.

[0022] (3) The degradable plastic prepared by the present invention can be degraded back to the original monomer under mild conditions, achieving 100% recovery of carbon resources. The obtained monomer can be repolymerized to obtain the corresponding polymer, achieving closed-loop recycling.

[0023] (4) The biodegradable plastics prepared by the present invention can be efficiently converted into several functional polymer materials, thereby achieving high-value conversion of waste plastics. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 In the figure, Figure A is the synthesis route of CP polymer; Figure B is the nuclear magnetic resonance hydrogen spectrum and carbon spectrum of CP28 in CP polymerization, as well as the characteristic peak positions of carbon-carbon double bonds of other polymers in the hydrogen spectrum and carbon spectrum; Figure C is the X-ray diffraction spectrum (XRD) of partially crystallized CP polymer; Figure D is the differential scanning calorimetry DSC test results of some polymers; Figure E is the small angle X-ray scattering spectrum (SAXS) of partially crystallized CP polymer.

[0026] Figure 2 In the figure, A is the relationship between the melting point Tm and the side chain length, B is the relationship between the lamella thickness lc and the melting point Tm, and C is the linear relationship between the lamella thickness lc and the side chain length.

[0027] Figure 3 In the figure, A is a schematic diagram of the reaction of CP28 degradation and monomer cyclic polymerization to obtain the polymer again, B is a physical picture of the sample strip of CP28 after the tensile test placed in THF, C is a physical picture of the degradation experiment after adding the catalyst, D is the precipitated product, E is the degradation product obtained after purification, F is the nuclear magnetic resonance hydrogen spectrum characterization diagram of the degradation product, and G is the gel permeation chromatography curve of the polymer and the product before and after degradation.

[0028] Figure 4 Figure A is a tensile test result of CP28, Figure B is a photo of CP28 after being made into a packaging bag, and Figure C is a photo of the packaging bag after being filled with water and desiccant (anhydrous MgSO4) for 15 days. DETAILED DESCRIPTION

[0029] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0030] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0032] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0033] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0034] In the following examples, room temperature refers to 23° C., and the raw materials used are all commercially available conventional raw materials, without any special limitation. The following description will not be repeated.

[0035] Example 1

[0036] (1) Synthesis of monomer CP9-M, the steps are as follows:

[0037]

[0038] Dichloromethane (DCM) (150 mL) and 3-cyclopentene-1-carboxylic acid (10 g, 89.2 mmol) were added to a 250 mL three-necked round-bottom flask equipped with a stirring bar and cooled to 0 ° C. N-nonanol (12.8 g, 1 equivalent, 89.2 mmol) was added, followed by 4-dimethylaminopyridine (DMAP) (0.7 g, 5.7 mmol). The mixture was stirred to dissolve. The dehydrating agent dicyclohexylcarbodiimide (DCC) (20.6 g, 100 mmol) was dissolved in another 50 mL DCM and then slowly transferred to the above solution. The resulting esterification reaction was carried out at 0 ° C for 2 hours, followed by another 2 hours at room temperature to complete the reaction. The reaction was then quenched by adding ether (100 mL) and deionized water (50 mL), and the organic phase was extracted three times with ether. The combined organic solution was washed with brine and dried over anhydrous MgSO4. The solvent was evaporated and the crude product was further purified by silica gel column chromatography using petroleum ether / ethyl acetate as eluent. After purification, nonylcyclopent-3-ene-1-carboxylate (CP9-M) (20 g) was obtained as a colorless liquid (yield 94%).

[0039] Characterization: 1 H NMR (400MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7Hz, 2H), 3.17–3.05 (m, 1H) ,2.65(d,J=8.2Hz,4H),1.68–1.57(m,2H),1.39–1.21(m,12H),0.92–0.84(m,3H). 13 C NMR (101 MHz, CDCl3, ppm): δ=176.28, 128.98, 64.68, 41.63, 36.31, 31.85, 29.47, 29.24 (d, J=2.4 Hz), 28.66, 25.91, 22.66, 14.09. High resolution mass spectrum HRMS: [M+H]+calcd for C15H27O2: 239.2021, found: 239.1911.

[0040] (2) Preparation of polymer CP9, the steps are as follows:

[0041]

[0042] Under nitrogen protection, CP9-M (11.9 g, 50 mmol) was dissolved in DCM (20 mL, 2.5 M) in a 50 mL dry Schlenk flask at room temperature. Hoveyda-Grubbs second generation catalyst (62.7 mg, 100 μmol) was then quickly added to the mixture, and the mixture was then cooled to 0 ° C. After two hours, 5 mL of ethyl vinyl ether was added to quench the reaction for 30 minutes. The solution was poured into 300 mL of methanol to precipitate the product. The pale yellow viscous solid product was dissolved in DCM and re-precipitated into another 300 mL of methanol. The product was then collected by centrifugation and vacuum dried to constant weight. Yield: polymer CP9, 9.4 grams (yield 79%).

[0043] Characterization: 1 H NMR (400MHz, CDCl3): δ = 5.44–5.28 (m, 2H), 4.02 (t, J = 6.7Hz, 2H), 2.45–2.00 ( m,5H),1.58(q,J=6.8Hz,2H),1.29(d,J=11.2Hz,12H),0.88(t,J=6.7Hz,3H). 13 C NMR (101MHz,CDCl3,ppm):δ=174.89,129.29,128.24,64.40(d,J=6.7Hz),45.78,34.67,31.87,29.52,29.29(d,J=2.1Hz),28.71,25.96(d,J=2.0Hz),22.67,14.11. Gel permeation chromatography GPC data (THF vs polystyrene standard):Mn=57.1kDa, Thermogravimetric analysis TGA: 335°C (5% weight loss). Differential scanning calorimetry DSC, melting point Tm = -65°C.

[0044] Using the same experimental steps as step (1) of Example 1, the present invention further synthesized the following monomers (in the preparation process of the following monomers, 3-cyclopentene-1-carboxylic acid was used as the matrix, the difference was that the type of alcohol was different, the amount of the selected alcohol was 89.2 mmol, and the weight increased accordingly with the chain length. The amounts of other reactants and reagents were the same as in step (1) of Example 1).

[0045] CP10-M

[0046]

[0047] CP10-M (21.4 g) (yield 95%). 11H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.11 (ddd, J = 16.4, 8.9, 7.5 Hz, 1H), 2.65 (d, J = 8.2 Hz, 4H), 1.64 (td, J = 14.5, 13.8, 7.6 Hz, 2H), 1.45 - 1.16 (m, 14H), 0.88 (t, J = 6.7 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.28, 128.98, 64.69, 41.64, 36.31, 31.89, 29.52, 29.27 (d, J = 5.1 Hz), 28.66, 25.92, 22.68, 14.10. HRMS: [M+H] + calcd for C 16 H 29 O2: 253.3023, found: 253.2217.

[0048] CP11 - M

[0049]

[0050] CP11 - M (20.5 g) (yield 86%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.18 - 3.02 (m, 2H), 2.65 (d, J = 8.2 Hz, 4H), 1.68 - 1.57 (m, 2H), 1.46 - 1.11 (m, 16H), 0.88 (t, J = 6.8 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.27, 128.98, 64.68, 41.64, 36.31, 31.91, 29.60, 29.54 (d, J = 5.4 Hz), 29.33, 29.25, 28.66, 25.92, 22.68, 14.10. HRMS: [M+H] + calcd for C 17 H 31 O2: 267.1422, found: 267.1156.

[0051] CP12 - M

[0052]

[0053] CP12 - M (22.6 g) (yield 90%).1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.17 - 3.05 (m, 1H), 2.65 (d, J = 8.2 Hz, 4H), 1.68 - 1.59 (m, 2H), 1.45 - 1.15 (m, 18H), 0.92 - 0.84 (m, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.29, 128.99, 64.70, 41.64, 36.32, 31.92, 29.64, 29.55 (d, J = 4.9 Hz), 29.35, 29.25, 28.66, 25.92, 22.69, 14.11. HRMS: [M + H] + calcd for C 18 H 33 O2: 281.2436, found: 281.2099.

[0054] CP14 - M

[0055]

[0056] CP14 - M (26.2 g) (yield 95%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.17 - 3.04 (m, 1H), 2.65 (d, J = 8.2 Hz, 4H), 1.63 (p, J = 7.3, 6.8 Hz, 2H), 1.45 - 1.12 (m, 22H), 0.88 (t, J = 6.7 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.27, 128.98, 64.69, 41.64, 36.31, 31.93, 29.67 (dd, J = 3.5, 1.4 Hz), 29.55 (d, J = 5.1 Hz), 29.37, 29.25, 28.66, 25.92, 22.70, 14.11. HRMS: [M + H] + calcd for C 20 H 37 O2: 309.2106, found: 309.1961.

[0057] CP16 - M

[0058]

[0059] CP16-M (25.4 g) (Yield 85%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.17 - 3.05 (m, 1H), 2.65 (d, J = 8.1 Hz, 4H), 1.68 - 1.57 (m, 2H), 1.26 (s, 26H), 0.88 (t, J = 6.7 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.30, 64.70, 41.65, 36.32, 31.94, 29.74 - 29.60 (m), 29.53, 29.37, 29.26, 28.67, 25.92, 22.70, 14.12. HRMS: [M + H] + calcd for C 22 H 41 O2: 337.4406, found: 337.2345.

[0060] CP18-M

[0061]

[0062] CP18-M (31.2 g) (Yield 96%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.17 - 3.04 (m, 1H), 2.65 (d, J = 8.2 Hz, 4H), 1.68 - 1.59 (m, 2H), 1.26 (s, 30H), 0.92 - 0.84 (m, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.28, 128.98, 64.70, 41.64, 36.32, 31.94, 29.84 - 29.60 (m), 29.56 (d, J = 5.2 Hz), 29.38, 29.26, 28.67, 25.93, 22.70, 14.12. HRMS: [M + H] + calcd for C 24 H 45 O2: 365.3232, found: 365.1238.

[0063] CP20-M

[0064]

[0065] CP20-M (33.3 g) (yield 95%). 1 H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.11 (t, J = 8.2 Hz, 1H), 2.65 (d, J = 8.1 Hz, 4H), 1.67 - 1.57 (m, 2H), 1.26 (s, 34H), 0.88 (t, J = 6.7 Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 176.30, 128.99, 64.71, 41.65, 36.32, 31.94, 29.82 - 29.64 (m), 29.56 (d, J = 5.2 Hz), 29.38, 29.26, 28.67, 25.93, 22.70, 14.13. HRMS: [M+H] + calcd for C 26 H 49 O2: 393.4021, found: 393.2302.

[0066] CP22-M

[0067]

[0068] CP22-M (34.9 g) (yield 93%). 1 H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.11 (ddd, J = 16.4, 8.9, 7.5 Hz, 1H), 2.64 (d, J = 8.2 Hz, 4H), 1.68 - 1.59 (m, 2H), 1.26 (s, 38H), 0.88 (t, J = 6.7 Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 176.33, 129.00, 64.72, 41.65, 36.33, 31.94, 29.70 (d, J = 2.1 Hz), 29.56 (d, J = 5.3 Hz), 29.37, 29.26, 28.67, 25.93, 22.70, 14.13. HRMS: [M+H] + calcd for C 28 H 53 O2: 421.2223, found: 421.1953.

[0069] CP24-M

[0070]

[0071] CP24-M (37.2 g) (Yield 93%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7 Hz, 2H), 3.11 (t, J = 8.2 Hz, 1H), 2.65 (d, J = 8.1 Hz, 4H), 1.68 - 1.51 (m, 2H), 1.25 (s, 42H), 0.88 (t, J = 6.7 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.32, 128.99, 64.71, 36.33, 31.94, 29.72, 29.59 - 29.45 (m), 29.38, 29.26, 28.67, 25.93, 22.71, 14.13. HRMS: [M + H] + calcd for C 30 H 57 O2: 449.2323, found: 449.1229.

[0072] CP28-M

[0073]

[0074] CP28-M (40.8 g) (Yield 91%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.66 (s, 2H), 4.08 (t, J = 6.8 Hz, 2H), 3.20 - 2.98 (m, 1H), 2.65 (d, J = 8.2 Hz, 4H), 1.67 - 1.55 (m, 2H), 1.25 (s, 50H), 0.92 - 0.84 (m, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 176.30, 128.99, 64.70, 41.65, 36.32, 31.95, 29.72, 29.56 (d, J = 5.3 Hz), 29.38, 29.27, 28.67, 25.93, 22.71, 14.13. HRMS: [M + H] + calcd for C 34 H 65 O2: 505.2324, found: 505.1966.

[0075] CP30-M

[0076]

[0077] CP30-M (43.2 g) (yield 96%). 1 H NMR (400MHz, CDCl3, ppm): δ = 5.67 (s, 2H), 4.09 (t, J = 6.8Hz, 2H), 3.20-2.99 (m, 1H),2.66(d,J=8.2Hz,4H),1.67-1.56(m,2H),1.25(s,54H),0.93-0.85(m,3H). 13 C NMR (101MHz, CDCl3, ppm): δ = 176.31, 129.00, 64.71, 41.65, 36.33, 31.95, 29. 71,29.56(d,J=5.3Hz),29.37,29.28,28.67,25.94,22.71,14.13.HRMS:[M+H] + Calculate for C 34 H 65 O2:533.2721,found:533.2237.

[0078] Using the same experimental steps as step (2) of Example 1, the present invention uses the above monomers to synthesize the following polymers:

[0079] CP10

[0080]

[0081] CP10 (9.7 g) (yield 77%). 1 H NMR (400MHz, CDCl3, ppm): δ = 5.43-5.26 (m, 2H), 4.02 (t, J = 6.7Hz, 2H), 2.24 (dddd, J = 47.3, 4 1.9,14.4,7.8Hz,5H),1.58(d,J=4.8Hz,2H),1.28(d,J=12.8Hz,14H),0.88(t,J=6.7Hz,3H). 13 C NMR (101MHz, CDCl3, ppm): δ = 174.91, 129.28, 128.26, 64.38, 45.79, 34.68, 31.90 ,29.58,29.31(d,J=2.8Hz),28.70,25.96(d,J=2.3Hz),22.68,18.39,14.11.GPC data(THF vs polystyrene standard):M n =64.4 kDa, TGA:340℃(5%weight loss).DSC:Tm = -61 °C.

[0082] CP11

[0083]

[0084] CP11 (5.4 g) (yield 81%). 1 H NMR (400 MHz, CDCl3, ppm): δ = 5.45 - 5.25 (m, 2H), 4.02 (t, J = 6.7 Hz, 2H), 2.45 - 2.02 (m, 5H), 1.66 - 1.49 (m, 2H), 1.28 (d, J = 13.3 Hz, 16H), 0.88 (t, J = 6.7 Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 174.91, 129.25, 128.27, 64.38, 45.80, 34.70, 31.92, 29.61 (d, J = 5.2 Hz), 29.33 (d, J = 5.1 Hz), 28.71, 25.97 (d, J = 2.3 Hz), 22.69, 18.40, 14.11. GPC data (THF vs polystyrene standard): M n = 70.8 kDa, TGA: 371 °C (5% weight loss). DSC: T m = -45 °C.

[0085] CP12

[0086]

[0087] CP12 (5.1 g) (yield 71%). 1 H NMR (400 MHz, CDCl3, ppm): δ = 5.44 - 5.25 (m, 2H), 4.02 (t, J = 6.7 Hz, 2H), 2.43 - 2.02 (m, 5H), 1.58 (q, J = 7.0, 6.3 Hz, 2H), 1.41 - 1.15 (m, 18H), 0.88 (t, J = 6.7 Hz, 3H). 1313C NMR (101 MHz, CDCl3, ppm): δ = 173.87, 128.26 (d, J = 4.6 Hz), 127.24, 63.40 (d, J = 7.1 Hz), 44.78, 33.69, 30.92, 28.79 - 28.48 (m), 28.33 (d, J = 5.6 Hz), 27.70, 24.96 (d, J = 2.3 Hz), 21.68, 17.40, 13.10. GPC data (THF vs polystyrene standard): M n = 91.2 kDa, TGA: 365 °C (5% weight loss). DSC: T m = -25 °C.

[0088] CP14

[0089]

[0090] CP14 (5.7 g) (yield 74%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.44 - 5.24 (m, 2H), 4.02 (t, J = 6.7 Hz, 2H), 2.44 - 2.01 (m, 5H), 1.59 (dd, J = 11.8, 5.2 Hz, 2H), 1.26 (s, 22H), 0.88 (t, J = 6.7 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 173.81 (t, J = 3.2 Hz), 128.26 (d, J = 5.2 Hz), 127.25, 63.37 (d, J = 6.7 Hz), 44.77, 33.68, 30.92, 28.79 - 28.51 (m), 28.34 (d, J = 5.6 Hz), 27.71, 24.97 (d, J = 2.2 Hz), 21.68, 13.11. GPC data (THF vs polystyrene standard): M n = 111.4 kDa, TGA: 369 °C (5% weight loss). DSC: T m = 3 °C.

[0091] CP16

[0092]

[0093] CP16 (2.9 g) (yield 69%). 11H NMR (400 MHz, CDCl3, ppm): δ = 5.47 - 5.22 (m, 2H), 4.01 (t, J = 6.8 Hz, 2H), 2.43 - 1.97 (m, 5H), 1.69 - 1.50 (m, 2H), 1.26 (s, 26H), 0.88 (t, J = 6.7 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 174.85, 129.28, 128.26, 64.37, 45.81, 34.72, 31.95, 29.89 - 29.60 (m), 29.37 (d, J = 4.7 Hz), 28.74, 25.99 (d, J = 2.4 Hz), 22.71, 18.44, 14.13. GPC data (THF vs polystyrene standard): M n = 111.6 kDa, TGA: 366 °C (5% weight loss). DSC: T m = 22 °C.

[0094] CP18

[0095]

[0096] CP18 (3.3 g) (yield 72%). 1 1H NMR (400 MHz, CDCl3, ppm): δ = 5.44 - 5.27 (m, 2H), 4.01 (t, J = 6.8 Hz, 2H), 2.46 - 1.97 (m, 5H), 1.70 - 1.49 (m, 2H), 1.26 (s, 30H), 0.88 (t, J = 6.8 Hz, 3H). 13 13C NMR (101 MHz, CDCl3, ppm): δ = 174.90, 129.28, 64.37, 45.78, 34.80, 31.95, 29.72 (d, J = 6.2 Hz), 29.37 (d, J = 4.1 Hz), 28.74, 26.01, 22.71, 14.13. GPC data (THF vs polystyrene standard): M n = 147.3 kDa, TGA: 368 °C (5% weight loss). DSC: T m = 37 °C.

[0097] CP20

[0098]

[0099] CP20 (3.6 g) (yield 73%). 1 H NMR (400 MHz, CDCl3, ppm): δ = 5.35 (s, 2H), 4.01 (t, J = 6.8 Hz, 2H), 2.46 - 1.98 (m, 5H), 1.56 (s, 2H), 1.26 (s, 34H), 0.88 (t, J = 6.8 Hz, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 174.82, 129.26, 128.28, 64.43, 64.36, 45.81, 34.73, 31.95, 29.77, 29.75, 29.69, 29.64, 29.39, 29.36, 28.74, 26.01, 25.99, 22.71, 14.13. GPC data (THF vs polystyrene standard): M n = 142.5 kDa, TGA: 379 °C (5% weight loss). DSC: T m = 47 °C.

[0100] CP22

[0101]

[0102] CP22 (4.05 g) (yield 77%). 1 H NMR (400 MHz, CDCl3, ppm): δ = 5.45 - 5.26 (m, 2H), 4.01 (t, J = 6.8 Hz, 2H), 2.46 - 1.95 (m, 5H), 1.57 (s, 2H), 1.26 (s, 38H), 0.95 - 0.81 (m, 3H). 13 C NMR (101 MHz, CDCl3, ppm): δ = 174.89, 129.27, 64.37, 45.79, 34.68, 31.95, 29.79 - 29.59 (m), 29.38 (d, J = 3.0 Hz), 28.75, 26.01, 22.71, 14.13. GPC data (THF vs polystyrene standard): M n = 146.9 kDa, TGA: 373 °C (5% weight loss). DSC: T m = 55 °C.

[0103] CP24

[0104]

[0105] CP24(4g)(Yield 72%). 1 H NMR(400MHz, CDCl3, ppm): δ = 5.35(p, J = 2.8Hz, 2H), 4.01(t, J = 6.7Hz, 2H), 2.46 - 2.01(m, 5H), 1.58(d, J = 5.4Hz, 2H), 1.25(s, 42H), 0.88(t, J = 6.7Hz, 3H). 13C NMR(101MHz, CDCl3, ppm): δ = 174.82, 129.26, 64.36, 45.82, 34.74, 31.95, 29.78, 29.75, 29.71, 29.69, 29.65, 29.39, 29.36, 28.75, 26.02, 22.71, 14.13. GPC data(THF vs polystyrene standard): M n = 126.4kDa, TGA: 378℃(5% weight loss). DSC: T m = 65℃.

[0106] CP28

[0107]

[0108] CP28(9.6g)(Yield 76%). 1 H NMR(400MHz, CDCl3, ppm): δ = 5.46 - 5.25(m, 2H), 4.02(q, J = 6.9Hz, 2H), 2.24(dd, J = 51.6, 37.0Hz, 5H), 1.56(s, 2H), 1.25(s, 50H), 0.88(t, J = 6.7Hz, 3H). 13 C NMR(101MHz, CDCl3, ppm): δ = 174.75, 129.28, 64.36, 45.82, 34.73, 31.95, 29.79, 29.76, 29.74, 29.72, 29.69, 29.65, 29.39, 29.37, 28.75, 26.02, 22.71, 14.13. GPC data(THF vs polystyrene standard): M n = 166.5kDa, TGA: 398℃(5% weight loss). DSC: T m = 75℃.

[0109] CP30

[0110]

[0111] CP30 (11.3 g) (yield 76%). 1 H NMR (400MHz, CDCl3, ppm): δ = 5.47-5.26 (m, 2H), 4.02 (q, J = 6.9Hz, 2H), 2.25 (dd, J = 51.6, 37.0Hz, 5H), 1.57 (s, 2H), 1.25 (s, 54H), 0.89 (t, J = 6.7Hz, 3H). 13 C NMR (101MHz, CDCl3, ppm): δ = 174.76, 129.28, 64.35, 45.83, 34.73, 31.96, 29.79, 29.7 7,29.74,29.72,29.70,29.65,29.40,29.37,28.75,26.01,22.73,14.12.GPCdata(THF vs polystyrene standard):M n =177.3 kDa, TGA:393℃(5%weightloss).DSC:T m =71 / 66℃.

[0112] Effect verification:

[0113] Differential scanning calorimetry (DSC) was used to measure the melting points (T m s) and melting enthalpy (ΔH m s) as shown in Table 1:

[0114] Table 1 Melting points of polymers at different heating and cooling rates (T m s) and melting enthalpy (ΔH m s)

[0115]

[0116] It can be seen from Table 1 that using differential scanning calorimetry (DSC), the melting point and melting enthalpy of the polymer at different heating and cooling rates are relatively stable.

[0117] Figure 1In the figure, Figure A is the synthesis route of the CP polymer of the present invention; Figure B is the nuclear magnetic resonance hydrogen spectrum and carbon spectrum of CP28 in CP polymerization, as well as the characteristic peak positions of carbon-carbon double bonds of other polymers in the hydrogen spectrum and carbon spectrum; Figure C is the X-ray diffraction spectrum (XRD) of the partially crystallized CP polymer; Figure D is the differential scanning calorimetry DSC test results of some polymers; Figure E is the small angle X-ray scattering spectrum (SAXS) of the partially crystallized CP polymer. As shown in Figure A, the polymer used in the present invention is relatively simple to synthesize and has low cost. The proportion of trans configuration in the carbon-carbon double bond of the obtained polymer is extremely high, at more than >90% (Figure B). In Figure C, the corresponding monomers of the crystallized polymer all present the same crystal form, that is, the orthorhombic crystal form. In contrast, although the polymer also presents an orthorhombic crystal form, due to the entanglement of the main chain, the growth of the (200) crystal plane corresponding to about 24.1° is inhibited, while the (110) crystal plane corresponding to about 21.3° is not affected. In Figure D, the melting curve obtained by differential scanning calorimetry (DSC) shows that as the number of carbon atoms in the side chain increases (i.e., the side chain becomes longer and longer), the melting point of the corresponding polymer becomes larger and larger, i.e., the thickness of the corresponding lamellae also becomes larger and larger. In Figure E, through SAXS testing, we obtained the corresponding scattering peak, from which the corresponding lamellae thickness can be calculated according to the volume crystallinity of the polymer.

[0118] Through the melting point, using the Thomson-Gibson equation, the relationship between the side chain length and the melting point, the thickness of the crystal, etc. is outlined, such as Figure 2 As shown, A is the relationship between the melting point Tm and the side chain length, B is the relationship between the lamella thickness lc and the melting point Tm, and C is the linear relationship between the lamella thickness lc and the side chain length.

[0119] Depend on Figure 2 It can be seen that the present invention can precisely control the crystalline properties of the prepared polymer, including the lamella thickness and melting point, by adjusting the length of the side chain.

[0120] Next, the present invention provides an implementation case of polymer material degradation and recycling of degradation products. Taking CP28 as an example, the reaction diagram of degradation and monomer cyclic polymerization to obtain polymer is as follows: Figure 3 As shown in Figure A. At room temperature, the CP28 specimen (0.5 g) after the tensile test was dissolved in tetrahydrofuran (THF) (10 mL) in a 25 mL dry Schlenk flask under nitrogen atmosphere. Figure 3 As shown in Figure B. Grubbs first generation catalyst (6.7 mg) was then quickly added to the mixture, and the mixture was then heated to 60°C. After reflux for 30 minutes, 2 mL of ethyl vinyl ether was added to quench the reaction for 30 minutes. After removing the solvent, a brown liquid product was obtained, as shown in Figure 3 As shown in Figure C, the precipitate product is obtained by precipitation, such as Figure 3The CP28-RM product was then purified by flash column chromatography and condensed and dried in vacuo to a constant weight, as shown in FIG. Figure 3 As shown in Figure E. Yield: 0.46 g (92%). The product was characterized by hydrogen nuclear magnetic resonance spectroscopy, as shown in Figure E. Figure 3 As shown in Figure F, it can be clearly seen that the product structure is clear before and after degradation, and the degradation proceeds smoothly. 1 H NMR (400MHz, CDCl3): δ = 5.66 (s, 2H), 4.08 (t, J = 6.7Hz, 2H), 3.10 (d, J = 8.7Hz, 1 H), 2.65 (d, J = 8.2Hz, 4H), 1.77-1.48 (m, 2H), 1.25 (s, 50H), 0.92-0.84 (m, 3H).

[0121] This monomer is repolymerized to obtain polymer CP28 (which may be named CP28-RP). 1 H NMR (400MHz, CDCl3, ppm): δ = 5.35 (d, J = 5.3Hz, 2H), 4.01 (t, J = 6.8Hz, 2H), 2.48– 2.03(m,5H),1.70–1.50(m,2H),1.25(s,50H),0.88(t,J=6.8Hz,3H).GPC data (THF vs polystyrene standard):Mn=93.9kDa, Figure 3 Figure G in the middle is the gel permeation chromatography curve of the polymer and product before and after degradation. After the polymer is degraded, the molecular weight is reduced to a small molecular monomer, and the monomer is repolymerized to obtain a high molecular polymer.

[0122] The mechanical properties of the polymer obtained by the present invention were tested, wherein the tensile test was carried out on an AI-Zooo-MJG universal testing machine of Gottech Testing Machine Company at room temperature (23°C) at a tensile rate of 50 mm / min until fracture. All polymer samples were processed by pressing the original material containing butylated hydroxytoluene and other antioxidants into a film and then cutting it. The results of more than three samples of each sample were compared. The sample was hot compressed at 160°C and 10 MPa pressure for 10 minutes using a flat vulcanizer, and then the sample was cooled to room temperature. A uniaxial tensile elongation test was carried out at room temperature at a tensile rate of 50 mm / min. The results obtained for CP28 are as follows: Figure 4As shown in Figure A, the tensile behavior of CP28 is more similar to that of low-density polyethylene (LDPE), but it is somewhat different from high-density polyethylene (HDPE) and linear low-density polyethylene (LLDPE). The yield point of the CP28 sample is about 7.5MPa, and the fracture strain of CP28 is 910%. Therefore, in terms of mechanical properties, CP28 is expected to become a recyclable substitute for LDPE. Figure B is a photo of CP28 made into a packaging bag, and Figure C is a photo of the packaging bag containing water and desiccant (anhydrous MgSO4) for 15 days. After 15 days, the mass of water and anhydrous MgSO4 remains unchanged, so it can be seen that this material can be used to make packaging bags to preserve substances well.

[0123] The properties of other polymers and CP28 prepared by the present invention can be changed accordingly according to the length of the side chain, and the melting point will decrease as the length of the side chain becomes shorter until it no longer crystallizes.

[0124] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.

Claims

1. A method for preparing degradable and recyclable plastics, characterized in that: The following steps are involved: The cyclopentene base is reacted with an alkyl alcohol or an alkyl acid to obtain a monomer, and then a ring-opening metathesis polymerization is carried out under the action of a catalyst to obtain the degradable and recyclable plastic.

2. The method for preparing degradable and recyclable plastic according to claim 1, characterized in that: The cyclopentene base includes one of 3-cyclopentene-1-carboxylic acid, 3-cyclopentene-1-methanol and 3-cyclopentene-1-ol.

3. The method for preparing degradable and recyclable plastic according to claim 2, characterized in that: When the cyclopentenyl base is 3-cyclopentene-1-methanol or 3-cyclopentene-1-ol, the corresponding alkyl acid includes one or more of octanoic acid, nonanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tetradecanoic acid, hexadecanoic acid, octadecanoic acid, eicosyl acid, docosyl acid, tetracosyl acid, hexacosyl acid, octacosyl acid, triacontyl acid and tridodecyl acid; when the cyclopentenyl base is 3-cyclopentene-1-carboxylic acid, the corresponding alkyl alcohol includes one or more of octyl alcohol, nonanol, decanol, undecyl alcohol, dodecyl alcohol, tetradecyl alcohol, hexadecyl alcohol, octacosyl alcohol, eicosyl alcohol, docosyl alcohol, tetracosyl alcohol, hexacosyl alcohol, octacosyl alcohol, triacontyl alcohol and tridodecyl alcohol.

4. The method for preparing degradable and recyclable plastic according to claim 1, characterized in that: The solvent for the esterification reaction includes one or more of dichloromethane, tetrahydrofuran, N,N-dimethylformamide and toluene; the solvent for the ring-opening metathesis polymerization includes one or more of dichloromethane, tetrahydrofuran, toluene, chlorobenzene and dichlorobenzene.

5. The method for preparing degradable and recyclable plastic according to claim 1, characterized in that: The catalyst includes a Grubbs first generation catalyst, a Grubbs second generation catalyst, a Grubbs third generation catalyst, a Hoveyda-Grubbs first generation catalyst or a Hoveyda-Grubbs second generation catalyst.

6. The method for preparing degradable and recyclable plastic according to claim 1, characterized in that: The temperature of the ring-opening metathesis polymerization is -10 to 0°C.

7. A degradable and recyclable plastic prepared according to the preparation method according to any one of claims 1 to 6.

8. A method for degrading recyclable plastics according to claim 7, characterized in that: The degradable and recyclable plastic is added into a solvent and degraded under the action of a catalyst to obtain a monomer.

9. The method for degrading recyclable plastics according to claim 8, characterized in that: The solvent includes tetrahydrofuran, dichloromethane, toluene, chlorobenzene, dichlorobenzene or n-hexane; the catalyst includes Grubbs first generation catalyst, Grubbs second generation catalyst, Grubbs third generation catalyst, Hoveyda-Grubbs first generation catalyst or Hoveyda-Grubbs second generation catalyst.

10. The method for degrading recyclable plastics according to claim 8, characterized in that: The degradation temperature is 23-80°C.

Citation Information

Patent Citations

  • Method for producing temperature-stable polyalkenylenes

    CN112154168A

  • Synthesis method of recyclable nitrogen-containing polycarbonate plastic

    CN112851924A

  • Preparation of ruthenium metal catalyst and application of ruthenium metal catalyst in ring-opening metathesis polymerization

    CN114957620A

  • Degradable polydicyclopentadiene thermosetting material containing silyl ether element and preparation method of degradable polydicyclopentadiene thermosetting material

    CN117343235A

  • Cyclopentenone derivative as well as synthesis method and application thereof

    CN117447356A

Cited By

  • Degradable and recyclable plastic as well as preparation method and application thereof

    CN120173214A